Aplicabilidade e limites das cláusulas de não concorrência nos contratos de franquia - Santos, Alexandre David (2016)
The topic of this paper is the relationship between the franchiser and the franchisee. Our goal is to explore the non-compete clauses to unveil how they are being adopted and applied by main franchisors in Brazil; finding its thresholds. Despite the system's maturity, we are living with the legal franchising framework for more than 20 years. From a legal point of view and technical quality of the franchise agreements, we still have a lot to evolve. The study and development of non- compete clauses can improve the franchising system. In this world, franchisors are business players and agreement developers and non-compete clauses that are most the times abusive, generic and subject to relativization by the judge, thus generating uncertainty in business relations between the parties. The role of the non-compete clause is to is to safeguard the franchisor, responsible for the business creation and development, know-how, production techniques and management templates have to be safeguarded, mostly from the ones interested in taking advantage and getting such expertise, after a short relationship with the franchisor. The relationship between the franchiser and the franchisee is rich and conducive to facilitating the franchisee entrepreneur - sometimes inexperienced in that activity - access to the know-how of the activity and means of trade specific business organization, the franchise object. Please note that the transfer of know-how is an immaterial element, key to the development of the activity of the franchise business. In this paper, our questioning turns to the possibility of preventing the use of know-how and activity developed by the former franchisee at the end of the contractual relationship in complex and specific contexts. The review of the ten franchising agreements corresponding to fifty percent of current industries is revealing. All non-compete clauses have worrying technical deficiencies. We noted the lack of key, strategic and efficiency requirements, which can mean the relativization or invalidity of non-compete clauses and as result, legal uncertainty. As practical solutions we present the proposed modulation of non-compete clauses by the essential, strategic and efficiency requirements, creating two different classes as a means to provide legal certainty for franchising agreements. We propose the revision of the legal franchising landmark.